Decoding diets: insights on ultra-processed food consumption among Lebanese adults from the updated LEBANese natiONal food consumption survey (LEBANON-FCS) - Khattar, Maroun; Tzenios, Nikolaos; Antar, Esraa; Malli, Dana; , The Adults-Lebanon-FCS Group; Hoteit, Maha (Frontiers in Nutrition, 2024)
Ultra-processed foods (UPF) are evident to play a role in the development of nutrition-related non-communicable diseases (NR-NCDs). There’s a scarcity of data in the Eastern Mediterranean Region (EMR) regarding UPF consumption. This study was conducted to assess the dietary pattern of Lebanese adults according to different degrees of food processing. A cross-sectional study involving a nationally representative sample (n=444) of Lebanese adults (18-64 years) was conducted over the course of 5 months. A validated FFQ and two non-consecutive 24-hour recalls were used to collect the dietary intake. Food items were classified according to the NOVA food classification system, and the percent contribution of every type of processing to the energy intake was calculated. UPF contributed to the highest percent of energy intake in the sample (46.7%), followed by unprocessed and minimally processed foods (39.6%). Being male, and younger increased the odds of higher UPF intake; being employed and food secure increased the odds of a higher NOVA-UPF score. Compared with participants in Beirut, participants residing in North Lebanon and Akkar had higher odds of having a high UPF intake and lower odds of having a high NOVA-UPF score. The three most contributing food items to energy intake were ultra-processed (breads and breakfast cereals, fast foods, sweets and desserts). Compared to the unprocessed and minimally processed food diet fraction, the UPF diet fraction was significantly higher in sodium and thiamin and lower in proteins, fiber, and essential vitamins and minerals such as vitamins A, D, B12, folate, iron, calcium, and magnesium. UPF intake was the main contributor to TEI, and the intake was considerably higher among those who reported having renal disease, younger adults, and males. In comparison to the minimally processed diet fraction, the UPF diet fraction was found to have considerably greater levels of sodium and thiamin and lower levels of proteins, fiber, and essential vitamins and minerals. The study findings call for public health policies to encourage the consumption of minimally processed foods and decrease the consumption of UPF, especially sweets and sweetened beverages, which are especially problematic.